Book Review: Muhammad Faishal Ibrahim and Peter J. Goldrick: Shopping Choices with Public Transport Options - Harry Timmermans (European Journal of Transport and Infrastructure Research, 2003)
This book has been motivated by the observation that by and large studies of spatial shopping behaviour have not taken into account transport mode, while most transport studies ignored the attributes of shopping centres. The study, described in this book represents an attempt to bridge this gap. To that effect, the authors try to identify and analyse the importance of different factors, which are taken into account by shoppers in their shopping centre choice in regions with a wide choice of public transport. In addition, they analyse shoppers' perceptions of transport modes in the context of shopping trips. They start however with a review of trends of retail decentralisation and transport planning.